Peters Syndrome: A diagnostic approach, clinical evolution and review - Aoyagi, Amanda Mayumi; Silva , Isabele Ferreira da; Martins, Amanda de Almeida; Ribeiro, Camilo de Lelis Lobo; Vieira, Yasmin de Amorim; Cardoso , Lara Caroline; Domingues, Matheus Mendonça; Branco , André Lages Gonçalves Castelo; Silva, Arianny Lima da; Miguel, Gabriel Cezar de Araujo; Reisdorfer, Verônika Carazzai; Bogaski, Luana Rafaela Saldanha; et al. (Seven Editora, 2024)
Introduction: Peters syndrome (or Peters anomaly, or anterior segment mesenchymal dysgenesis) is a rare and congenital genetic condition, described by Arthur G. H. Peters in 1906, which affects the anterior ocular mesenchymal segment, presenting varying degrees of corneal opacity, iridocorneal synechiae, presence of anterior chamber narrowing and Descemet's membrane defect. Case Presentation: A 6-year-old boy, born in Goiânia, state of Goiás, with a term birth and no history of previous health problems, was referred to our service by a general practitioner due to reduced visual acuity (VA) problems in both eyes and strabismus. The mother, who accompanied him, reported that the symptoms of strabismus began approximately a year and a half ago. She also mentioned that she was properly vaccinated during pregnancy against infections that could cause birth defects and denied any complications during pregnancy or childbirth. There is no relevant family history of eye diseases.Discussion: Because it is a rare anomaly, epidemiological data are scarce in the world literature, the only constant data is that the bilateral presentation is present in most cases. In this summary, we will address the main aspects of Peters syndrome, including its pathophysiology, classification, clinical characteristics, diagnosis and treatment. It is a syndrome that requires multidisciplinary evaluation to treat systemic complications, in some cases requiring a surgical approach such as penetrating keratoplasty and glaucoma treatment. Conclusion: The treatment varies according to the presentation of the condition and the genetic and multidisciplinary evaluation is of paramount importance in these patients. DOI:https://doi.org/10.56238/sevened2023.006-143